Planning and Managing Scientific Research - Kennett, Brian (ANU Press, 2014)
Although there are many books on project management, few address the issues associated with scientific research. This work is based on extensive scientific research and management experiences and is designed to provide an introduction to planning and managing scientific research for the beginning researcher. The aim is to build an understanding of the nature of scientific research, and the way in which research projects can be developed, planned and managed to a successful outcome. The book is designed to help the transition from being a member of a research team to developing a project and making them work, and to provide a framework for future work. The emphasis of the book is on broadly applicable principles that can be of value irrespective of discipline. It should be of value to researchers in the later stages of Ph.D. work and Postdoctoral workers, and also for independent researchers.